On the Dynamics of Solutions of Non-linear Recursive System - Kose, H.; Uslu, K.; Taskara, N.; Hekimoglu, O. (Communications in Mathematics and Applications, 2010)
In this paper, we have studied and examined the periodicity of solutions of rational difference equation system. Then we obtained equilibrium points of this difference equation system and investigated the behaviour of this system related to equilibrium points.
Keywords: Rational difference equation; Non-linear difference equation system; Period; Equilibrium point